The Silver Lining Methodology - Castillo Chamorro, José Miguel (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The way in which Strategic planning is designed is different depending on the organization. For that reason, no standard procedures can be given to develop Strategic planning. However, the scenarios analysis method is used in any field or organization. We could define a scenario as a set of variables or events that describes a future situation. Additionally, the continuous irruption of new technologies invites us to carry out a revision of the old methodologies and procedures with the intention of starting an innovation process to make them more efficient. The challenge presented in this article consists of the use of the agents technology within a new methodological approach to envision future possible scenarios more quickly and more accurately than the classical methods we currently use.
Keywords: foresight; strategic planning; agents technology; methodology; IJIMAI